2022
DOI: 10.1172/jci.insight.154402
|View full text |Cite
|
Sign up to set email alerts
|

RB expression confers sensitivity to CDK4/6 inhibitor–mediated radiosensitization across breast cancer subtypes

Abstract: Standard radiation (RT) therapy does not reliably provide locoregional control for women with multi-node positive and triple-negative (TNBC) breast cancers. We hypothesized that CDK4/6 inhibition (CDK4/6i) would increase the radiosensitivity not only of estrogen receptor positive (ER+) cells, but also TNBC that express retinoblastoma (RB) protein. We found that CDK4/6i radiosensitized RB wild-type TNBC (n=4, rER 1.49 -2.22), but failed to radiosensitize RB-null TNBC (n=3, rER: 0.84 -1.00). RB expression predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…CRISPR cell lines were generated using the lentiCRISPRv2 plasmid (Addgene #98291) and the AR guide sequence (5’ CACCTCCAGCTTGATGCGAGCGTG 3’). As previously described [ 28 ], the lentiCRISPRv2 plasmid was digested with BsmB1 for 15 min at 55 degrees and gel-purified using the QIAquick Gel Extraction Kit (Qiagen #28706X4). Oligonucleotides were obtained from Integrated DNA Technologies and annealed at 95 degrees then cooled at 5 degrees/min.…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR cell lines were generated using the lentiCRISPRv2 plasmid (Addgene #98291) and the AR guide sequence (5’ CACCTCCAGCTTGATGCGAGCGTG 3’). As previously described [ 28 ], the lentiCRISPRv2 plasmid was digested with BsmB1 for 15 min at 55 degrees and gel-purified using the QIAquick Gel Extraction Kit (Qiagen #28706X4). Oligonucleotides were obtained from Integrated DNA Technologies and annealed at 95 degrees then cooled at 5 degrees/min.…”
Section: Methodsmentioning
confidence: 99%
“…The first checkpoint prevents the cell from advancing past the G1 phase, which happens between the G1 and S (synthetic) phases [26]. The retinoblastoma (Rb) gene encodes a protein that has been demonstrated to be important for this [27]. When activated, this tumor suppressor protein (pRb) binds to E2F transcription factors, preventing them from participating in cell replication.…”
Section: G1 Phasementioning
confidence: 99%
“…The Rb pathway has been identified as a potential cancer treatment target. pRb, like many other cell cycle-regulating molecules, is phosphorylated to an inactive state by cyclin-dependent kinases (CDKs) [27]. This allows pRb to dissociate from the transcription factors mentioned above and exert its impact on the cell's transcription machinery.…”
Section: G1 Phasementioning
confidence: 99%
“…We and others have shown that RT and CDK4/6 inhibitors can be safely combined and mediate additive-to-synergistic therapeutic effects in a variety of tumor models, including cultured human and mouse cancer cells, as well as human tumors xenografted in immunodeficient mice and mouse tumors evolving in immunocompetent syngeneic hosts [ 24 31 ]. Importantly, some of these studies revealed the relevance of treatment schedule on therapeutic efficacy [ 24 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%